Studi Tentang Penyelenggaraan Kelompok Belajar Pendidikan Dasar Ut Di Daerah Dalam Perspektif Teori Negotiated Order - Surasmi, Wuwuh Asrining (Penerbit STKIP PGRI Bangkalan, 2018)
This study examines the negotiation in the management Pendas Program according to the theoretical perspective of Negotiated Order Anselm Strauss, especially the negotiated order that occurs in the implementation of the program between the manager and the students in Ponorogo, Madiun, Ngawi East Java. The management implements an independent system, the learning group must play an active role in fulfilling the obligations of the UT program. Funds from UT funding are not sufficient for school building rental costs. In order for the conduct to take place well, the managers and students entered into agreements for management fees outside of the financing contained in the UT. This research uses qualitative method, data retrieval with observation, interview, and documentation with research subject that is student, manager of study group. While the data analysis using Miles and Hubermann theory with the steps of Data Collection, Reduction, Display, Conclution. Results show that between students and Pokjar an agreement is reached with additional financing for the smoothness of the activities and the feasibility of additional services beyond the UT policy. This agreement has consequences for additional costs to be incurred by students for these purposes by obtaining good service. Partial obstacles come from students who have a different understanding with most UT students and pokjar executives as well as Tutor UT. Constraints can be overcome and resolved well with negotiated order.